Corruption and tax burden: What is the joint effect on total factor productivity? - Kouramoudou Kéïta; Hannu Laurila (Economies, 2021)
A common conclusion in the literature is that both corruption and taxation hamper economic growth. It is also plausible that both affect total factor productivity, which, by the famous Solow residual, is a vital driver of economic progress. Moreover, corruption and tax burden are supposed to be intertwined. This paper focuses on the supposedly linked effects of corruption and tax burden on total factor productivity. The empirical study uses panel data from 90 countries for the time span of 1996-2014. The results show that both corruption and tax burden deteriorate total factor productivity, but that an increase in tax burden mitigates the negative effect of corruption.
Keywords: 330; corruption; Solow residual; tax burden; total factor productivity